Evaluasi Implementasi Sistem Akuntabilitas Kinerja Instansi Pemerintah (Sakip) Di Biro Hukum Pemprov Kepri - Dwi Septi Haryani (Jurnal Bangkit Indonesia, 2019)
All Government Agencies have to arrange the Performance Report every year. That is a form of the affirmation of the Performance Accountability has been done by the application of accountability system of the government agency performance (SAKIP). SAKIP is one of program to Bureaucrat Reformation. For knowing how far the government instances to implement the SAKIP and also to support that there is the raising of government performance, so it is important to do the evaluation of Implementation of SAKIP. This research is for knowing how the evaluation of the implementation of accountability system of the government agency performance (SAKIP) at Law Government Office, Kepri Province. The method of this research uses literature study by journal, book, article and also interview the resource directly. The result of the research is to show that SAKIP has a function to make easier in monitoring and making working plan, reporting and evaluating the performance. SAKIP is done by Law Government Office, Kepri Province has done as the expectation. So, it can help the Government to create the region development.